Pengaruh Model Pembelajaran Bersiklus Terhadap Motivasi Belajar Pendidikan Agama Kristen Dan Budi Pekerti Siswa Kelas XI SMA Negeri 1 Tampahan Tahun Pembelajaran 2023/2024 - Exaudi Dian Mayawie Napitupulu; Goklas J. Manalu; Frainskoy Rio Naibaho; Wilson Simanjuntak; Taripar Aripin Samosir (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
This research aims to determine the effect of the cyclical learning model on PAK learning motivation and character of class XI students at SMA Negeri 1 Tampahan in the 2023/2024 academic year. The hypothesis of this research is that there is a positive and significant influence in the use of the cyclical learning model on the PAK learning motivation and character of class XI students at SMA Negeri 1 Tampahan for the 2023/2024 academic year. This research uses an experimental type research method with a pre-experimental research design in the form of